2017
DOI: 10.1371/journal.pone.0189303
|View full text |Cite
|
Sign up to set email alerts
|

Conservation and divergence of Starch Synthase III genes of monocots and dicots

Abstract: Starch Synthase (SS) plays an important role in extending the α-1,4 glucan chains during starch biosynthesis by catalyzing the transfer of the glucosyl moiety from ADP-glucose to the non-reducing end of a pre-existing glucan chain. SS has five distinct isoforms of which SSIII is involved in the formation of longer glucan chain length. Here we report identification and detailed characterization of ‘true’ orthologs of the well-characterized maize SSIII (ZmSSIII), among six monocots and two dicot species. ZmSSIII… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 31 publications
0
10
0
Order By: Relevance
“…Both iodine binding and SEC revealed substantial elevations of amylose in the triple mutant, and SEC also revealed smaller but signi cant elevation in the double mutants (iodine binding: 35.1% for triple mutants vs. 26.0% in sibling controls; SEC: 33.8% for triple mutants and 29.3% for double mutants vs. 25.5% in sibling controls). The double and triple mutants also had fewer long amylopectin chains; this was anticipated given the proposed role of SSIII in producing longer length amylopectin chains by extending short chains produced by SSI 39 . Prior studies of ssIIIa mutants in maize and rice also found that the mutants had fewer long amylopectin chains 18,21 .…”
Section: Discussionmentioning
confidence: 80%
“…Both iodine binding and SEC revealed substantial elevations of amylose in the triple mutant, and SEC also revealed smaller but signi cant elevation in the double mutants (iodine binding: 35.1% for triple mutants vs. 26.0% in sibling controls; SEC: 33.8% for triple mutants and 29.3% for double mutants vs. 25.5% in sibling controls). The double and triple mutants also had fewer long amylopectin chains; this was anticipated given the proposed role of SSIII in producing longer length amylopectin chains by extending short chains produced by SSI 39 . Prior studies of ssIIIa mutants in maize and rice also found that the mutants had fewer long amylopectin chains 18,21 .…”
Section: Discussionmentioning
confidence: 80%
“…The different levels of amylose observed in double vs. triple mutants may be of particular interest for wheat breeding applications and open new possibilities for fine-tuning amylose levels in wheat using unique combinations of mutant ssIIIa homoeologues. The double and triple mutants also had fewer long amylopectin chains; this was anticipated given the proposed role of SSIII in producing longer length amylopectin chains by extending short chains produced by SSI 43 . Prior studies of ssIIIa mutants in maize and rice also found that the mutants had fewer long amylopectin chains 20 , 23 .…”
Section: Discussionmentioning
confidence: 80%
“…There are either one or two coiled-coil (Cc) motifs in SSIII, SSIV, and SSV in the Nterminal region, which play an essential role in protein-protein interactions [84]. In SSIII, three conserved binding modules (CBM-25) are detected in the N-terminal region and play an important role in substrate binding [85]. The secondary structure of SS isoforms of maize was developed on the basis of the reference model of SSI in wheat, which showed 83% similarity to maize SSI [86].…”
Section: Structure-function Relationships Of Ss In Cerealsmentioning
confidence: 99%